A randomized clinical trial on the antitumoral effects of low molecular weight heparin in the treatment of esophageal cancer. Issue 4 (26th October 2018) - Taghizadeh Kermani, Ali; Hosseini, Sare; Fanipakdel, Azar; Joudi Mashhad, Mona; Akhavan Rezayat, Kambiz; Zardadi, Mahdi; Gholami, Arezoo; Javadinia, Seyed Alireza; Ferns, Gordon A.; Avan, Amir
Abstract: The current treatment approaches for esophageal cancer are associated with poor survival, and there are ongoing efforts to find new and more effective therapeutic strategies. There are several reports on the antitumoral effects of low‐molecular‐weight heparins (LMWHs). We have assessed the possible survival benefit of LMWHs in esophageal malignancies. This was a randomized, single‐blind, multicenter, Phase II clinical trial on nonmetastatic esophageal cancer candidate for neoadjuvant chemoradiotherapy. Patients were randomly assigned to the chemoradiotherapy‐only arm or chemoradiotherapy plus enoxaparin arm using 1:1 allocation. Radiotherapy was delivered in 1.8‐Gy daily fractions to a dose of 50.4 Gy in both groups. Paclitaxel 50 mg/m 2 and carboplatin (AUC 2) were administered weekly, concurrent with radiotherapy. In the intervention group, patients received enoxaparin (40 mg) and chemoradiation daily. 4–6 weeks after treatment, all patients underwent esophagectomy. After a median follow up of 7 months, estimated 1 year disease‐free survival (DFS) in the intervention group was 78.9% and was 70% in the control groups ( p  = 0.5). Toxicity from the experimental treatment was minimal, and there were no treatment‐related deaths. A pathologically complete response in intervention and control group was 64.8% and 62.5%, respectively ( p  = 0.9). There was a nonsignificant trend toward improved survival by the addition of enoxaparin to the concurrent chemoradiotherapy regimen. However, 1 y DFS of both groups were high as expected. A longer follow‐up and a larger sample size are required. Abstract : Text and image files are complete and in correct format(s) for production